Multiplex-PCR protocol development for rapid screening of white spot syndrome virus (WSSV) in shrimp - Sharmin Aktar; Md. Shahin Parvez; H M Rakibul Islam; Md. Nazmul Ahsan (Journal of Fisheries, 2020)
This study was aimed to develop a faster single step multiplex PCR protocol for the simultaneous detection of white spot syndrome virus (WSSV) with its host (i.e. shrimp) as internal positive control. To do so, four combinations of primer were tested (I. 16S rRNA+Lo F1R1; II. 16S rRNA+Lo F2R2; III. 16S rRNA+Lo F1R2; IV. 16S rRNA+Lo F2R1) which were selected based on two pairs of WSSV specific primer (Lo F1R1 and Lo F2R2) and one pair of shrimp specific primer (16S rRNA). DNA extracted from WSSV infected shrimp were amplified by PCR in a single tube using each of the primer combinations and the thermal cycling conditions as well as reagent compositions were optimized. All the primer combinations yielded their expected band sizes with stronger band resolution intensity that indicated the development of four multiplex PCR protocols. The developed multiplex protocols reduced the chance of cross contamination and these were found to be faster, single step and unique with less effort and resource use. Considering sensitivity and specificity, among the protocols, we suggested the protocols based on 16S rRNA+Lo F1R1 and/or 16S rRNA+Lo F2R2 primer combinations for rapid and routine screening of WSSV in shrimp PL, juvenile and adult.